Journey from cloud of things to fog of things: Survey, new trends, and research directions. (24th October 2022) - Chakraborty, Ananya; Kumar, Mohit; Chaurasia, Nisha; Gill, Sukhpal Singh
Abstract: With the advent of the Internet of Things (IoT) paradigm, the cloud model is unable to offer satisfactory services for latency‐sensitive and real‐time applications due to high latency and scalability issues. Hence, an emerging computing paradigm named as fog/edge computing was evolved, to offer services close to the data source and optimize the quality of services (QoS) parameters such as latency, scalability, reliability, energy, privacy, and security of data. This article presents the evolution in the computing paradigm from the client‐server model to edge computing along with their objectives and limitations. A state‐of‐the‐art review of Cloud Computing and Cloud of Things (CoT) is presented that addressed the techniques, constraints, limitations, and research challenges. Further, we have discussed the role and mechanism of fog/edge computing and Fog of Things (FoT), along with necessitating amalgamation with CoT. We reviewed the several architecture, features, applications, and existing research challenges of fog/edge computing. The comprehensive survey of these computing paradigms offers the depth knowledge about the various aspects, trends, motivation, vision, and integrated architectures. In the end, experimental tools and future research directions are discussed with the hope that this study will work as a stepping‐stone in the field of emerging computing paradigms.